Research to evaluate safety and impact of long COVID intervention with Ensitrelvir for National Cohort (RESILIENCE Study): A protocol for a randomized, double-blind, placebo-controlled trial - Konishi, Keiji; Yamamoto, Shungo; Sada, Ryuichi Minoda; Asano, Kento; Onozuka, Daisuke; Tanaka, Shintaro; Miyazawa, Shogo; Kinoshita, Masahiro; Kutsuna, Satoshi (PLOS ONE, 2025)
Long COVID, characterized by persistent symptoms following acute coronavirus disease (COVID-19), presents a substantial challenge to global health. Ensitrelvir fumarate, a novel oral antiviral agent, has demonstrated efficacy in treating of mild-to-moderate COVID-19. This study aims to evaluate the efficacy and safety of ensitrelvir in the prevention of Long COVID in patients without risk factors for severe COVID-19. This multi-center, randomized, double-blind, placebo-controlled trial adopts a decentralized clinical trial design, with participants recruited through partner healthcare institutions. Adults with mild COVID-19 will be randomized within 72 hours of symptom onset in a ratio of 1:1 to receive ensitrelvir (375 mg on day 1, followed by 125 mg once daily on days 2–5) or placebo. The primary efficacy endpoint is the proportion of patients with either “symptoms of fatigue, shortness of breath, difficulty breathing, or disturbances in smell or taste at 1 and 3 months post-treatment initiation” or “symptoms of difficulty with concentration and thinking, difficulty of reasoning and solving problems, or memory loss at 3 months post-treatment initiation”. Secondary endpoints include combinations of various symptoms, quality of life, and work productivity. The target sample size is 2,000 participants. This trial will generate data on the potential of ensitrelvir to prevent Long COVID, with important implications for patient care and public health. The decentralized design enables efficient data collection and minimizes participant burden. Trial registration This study was registered with the Japan Registry of Clinical Trials on February 16, 2024 (jRCTs051230184, https://jrct.mhlw.go.jp/en-latest-detail/jRCTs051230184).